Efficient Use of Clickers: A Mixed-Method Inquiry with University Teachers - George Cheung; Kelvin Wan; Kevin Chan (MDPI AG, 2018)
With the advancement of information technology and policies encouraging interactivities in teaching and learning, the use of students' response system (SRS), commonly known as clickers, has experienced substantial growth in recent years. The reported effectiveness of SRS has varied. Based on the framework of technological-pedagogical-content knowledge (TPACK), the current study attempted to explore the disparity in efficiency of adopting SRS. A concurrent mixed method design was adopted to delineate factors conducive to efficient adoption of SRS through closed-ended survey responses and qualitative data. Participants were purposefully sampled from diverse academic disciplines and backgrounds. Seventeen teachers from various disciplines (i.e., tourism management, business, health sciences, applied sciences, engineering, and social sciences) at the Hong Kong Polytechnic University formed a teacher focus group for the current study. In the facilitated focus group, issues relating to efficient use of clickers, participants explored questions on teachers' knowledge on various technologies, knowledge relating to their subject matters, methods and processes of teaching, as well as how to integrate all knowledge into their teaching. The TPACK model was adopted to guide the discussions. Emergent themes from the discussions were extracted using NVivo 10 for Windows, and were categorized according to the framework of TPACK. The survey, implemented on an online survey platform, solicited participants on teachers' knowledge and technology acceptance. The close-ended survey comprised 30 items based on the Technological Pedagogical Content Knowledge (TPACK) framework and 20 items based on the Unified Theory of Acceptance and Use of Technology (UTAUT). Participating teachers concurred with the suggestion that use of clickers is instrumental in engaging students in learning and assessing formative students' progress. Converging with the survey results, several major themes contributing to the successful implementation of clickers, namely technology, technological-pedagogical, technological-content, technological-pedagogical-content knowledge, were identified from the teacher focus groups. The most and second most frequently cited themes were technological-pedagogical-content Knowledge and the technological knowledge respectively. Findings from the current study triangulated with previous findings on TPACK and use of clickers, particularly, the influence of technological-pedagogical-content Knowledge and technological knowledge on successful integration of innovations in class. Furthermore, the current study highlighted the impact of technological-pedagogical and technological-content knowledge for further research to unfold technology adoption with these featured TPACK configurations, as well as rendering support to frontline academics related to integration of technology and pedagogy.